Observation of the shock‐induced β‐Sn to b.c.t.‐Sn transition using time‐resolved X‐ray diffraction. (7th December 2018) - Briggs, R.; Torchio, R.; Sollier, A.; Occelli, F.; Videau, L.; Kretzschmar, N.; Wulff, M.
Abstract : Time‐resolved X‐ray diffraction measurements were carried out on dynamically compressed Sn at the ID09 beamline of the European Synchrotron Radiation Facility. Using an infra‐red laser (up to 180 mJ at 1064 nm) with a 5 ns Gaussian pulse shape, the high‐pressure β‐Sn to b.c.t.‐Sn phase transition was observed using a single X‐ray bunch from the synchrotron. Abstract : Time‐resolved X‐ray diffraction measurements have been carried out on dynamically compressed Sn up to a maximum pressure of ∼13 GPa at the European Synchrotron Radiation Facility. The phase transition from β‐Sn to body‐centered tetragonal (b.c.t.) Sn has been observed using synchrotron X‐ray diffraction for the first time undergoing shock compression and release. Following maximum compression, the sample releases to lower pressures for several nanoseconds until the reverse transition occurs. The data are in good agreement with previous shock boundaries that indicate that the β‐Sn phase is stable ∼2 GPa higher than the static boundary upon compression and the b.c.t.‐Sn phase is stable ∼1 GPa lower upon release. The transition to the high‐pressure phase reveals a loss of texture in the X‐ray diffraction data from the `quasi' single‐crystal β‐Sn structure to a more powder‐like Debye–Scherrer ring.